Preventive foot self-care practice and associated factors among diabetic patients attending the university of Gondar comprehensive specialized referral hospital, Northwest Ethiopia, 2021 - Enyew Getaneh Mekonen; Tizita Gebeyehu Demssie (BMC Endocrine Disorders, 2022)
Abstract Background Diabetes mellitus is emerging as a major worldwide health problem that has a social, financial, and developmental impact on developing countries. Foot complications are among the most serious and costly complications of diabetes which lead to lower extremity amputation due to diabetic foot ulcers. Poor diabetic foot self-care practice is identified by different studies as a major contributing factor to diabetic foot ulcers. Therefore, this study was intended to assess foot self-care practice and associated factors among diabetic patients attending the University of Gondar comprehensive specialized referral hospital. Methods A hospital-based cross-sectional study was conducted from July 1 to August 30, 2021, at the University of Gondar comprehensive specialized referral hospital. A systematic random sampling technique was employed to select 384 diabetic patients. A structured pretested interviewer-administered questionnaire was used to collect data. The data was entered in epi-info version 7, analyzed using SPSS version 21, and presented using frequencies, percentages, tables, and graphs. Bivariable and multivariable analyses were investigated using a binary logistic regression model. P-value < 0.05 and an odds ratio with a 95% confidence interval were used to determine the significance and strength of the association. Results Of the 384 diabetic patients, 46.4% (95% CI (41.1%-51.6%)) of them had poor foot self-care practice. Being male [AOR = 0.54, 95% CI (0.32, 0.89)], couldn’t read and write and completed primary education [AOR = 2.35, 95% CI (1.01, 5.43)] & [AOR = 2.92, 95% CI (1.39, 6.12)], living in rural area [AOR = 3.84, 95% CI (1.91, 7.75)], having diabetic complications [AOR = 2.19, 95% CI (1.07, 4.46)], taking both injection and pills [AOR = 0.33, 95% CI (0.12, 0.88)], having previous information about foot care [AOR = 0.12, 95% CI (0.06, 0.24)], and family support [AOR = 0.57, 95% CI (0.34, 0.94)] were determinants of poor foot self-care practice. Conclusion The adherence of diabetic patients toward foot self-care practice was poor. Being male, having low educational status, living in a rural area, having diabetic-related complications, taking both injections and pills, not having previous information about foot care, and having poor family support increases the odds of having poor foot self-care practice. Giving health education to patients and their caregivers about the basic principles of diabetes foot care, like regular inspection of feet and appropriate footwear at their regular follow-up time, should be emphasized.